(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This is a critical review of two major phonological theories: linear natural phonology and the nonlinear optimality theory. Natural phonological theory asserts that phonological processes are phonetically based. Phonological error patterns help organize treatment targets and assess generalization. However, the natural phonology’s explanation of speech sound learning in children does not attain the status of a scientific theory. Process proliferation and poor definitions are other limitations. Optimality theory proposes that speech sounds may be marked (complex, more difficulty to produce, etc.) or unmarked (simple, easier to produce, etc.). Optimality replaces rules with markedness and faithfulness constraints. Constraints are common to all languages, but their ranking are unique to each language.